Registration of positron emission tomography (PET) image and functional near infrared spectroscopy (fNIRS) data - Fairuz Mohd Nasir
Functional Near-Infrared Spectroscopy (fNIRS) and Positron Emission Tomography (PET) is the imaging technique that gives functional information, especially for imaging the brain activity. The objective of this PhD project is to register fNIRS signals on the PET image. fNIRS measures oxyhaemoglobin and deoxyhaemoglobin in blood while PET measure the physiological function of the human body such as measuring the glucose consumption in the active area of the brain. fNIRS has high temporal resolution while the PET image has better spatial resolution compared to fNIRS. However, fNIRS measures haemodynamic changes in the cortex region but not in deeper brain structures. Thus, the proposed registration methods of fNIRS and PET is to improve the specificity given by both methods. The registration is based on a hardware-based system which used an optical tracking system; Polaris. The proposed method was validated using a fNIRS-PET phantom. Thereafter, the registration of fNIRS on PET image was performed on eleven subjects where each subject undergoes fNIRS examination along with the fNIRS task and then PET scan. To register the fNIRS probe on the PET image, we did a several series of the transformation of fNlRS probe coordinate into the PET coordinate. Polaris markers were used as the references marker to determine the transformation matrixes. The fNIRS probe was registered on the PET image using the in-house software and the activation area during the fNlRS task can be view on the PET image. The registration done in this study is successful as we can view the fNIRS activation area on the PET image.